Proficient Cloud Based Authenticated Database Scheme for Web services - *2 , Ms. Abirami.S., @3, Mrs. Evangeline. S #1 , Mr. S.Vijayanand (International Journal of Scientific Research and Management (IJSRM), 2017)
— In this research article, I support the disguise access control scheme and propose a new decentralized providesecure data storage clouds. Under the proposed scheme the cloud data storage without knowing the identity of the user toverify the authenticity of the series. My plan is to decrypt the information can be stored for only a valid user access control.The program prevents replay attacks and the creation, modification and supports reading data deposited in the cloud. Wecancelled a lecture by the user. Also, the clouds are designed as centralized authentication and access control and accesscontrol programs, our program is a versatile and robust. Communication, computation, and storage costs are comparable tocentralized approaches.